Seasonal variation in the number of human births at sea level and at altitude. Evidence of one circanual reproductive rate? - Paredes, Fredy (2015)
To determine whether there is a seasonal pattern in the number of births at sea level and at altitude. METHODOLOGY: A descriptive study of all births both at sea level (district of Trujillo 34 meters) and height (3,850 meters Quiruvilca district), between 1 January 1984 and December 31, 1993 was performed. adjusted monthly percentage of total annual births was used. 82.517 births were studied in total sea level and 4,055 in height. RESULTS: At sea level the biggest monthly percentage of the total annual number of births is found in the month of September at 9.3% and the lowest percentage in November to 7.9%. In height, these values correspond to the months of August and December (9.0% and 7.2%, respectively). CONCLUSION: variation patterns similar to both sea level and at altitude, found with higher values corresponding to the months of the calendar winter and spring under the births station is appreciated.